A influência da certificação ambiental sobre as vantagens de internacionalização do setor madeireiro brasileiro - Tripoli, Angela Cristina Kochinski (2014)
This research analyzes the influence of environmental certification on the advantages of internationalization of the logging industry. Using statistical data export obtained from Brazilian Federal Revenue Service from methods with, the Forest Stewardship Council (FSC), which is the most widespread seal the Brazilian forest sector and a case study, was possible to understand that the Brazilian timber companies, even if confronting one of larger areas of forest cover in the world, they have no comparative advantage as a whole, and that certification, in fact, extends the advantage in the international market the company. In this sense certification can be seen as an advantage of ownership of the company within the concepts of the Theory of Eclectic Paradigm of Dunning.